Milk Pie Production Management System in The MSME (UMKM) Sector in Denpasar (Case Study: UMKM CV. NAJWA) - Al Sabet, Fia Birtha (ProBisnis : Jurnal Manajemen, 2024)
MSME (UMKM)s (Micro, Small and Medium Enterprises) are the driving force of the economy in Indonesia, especially in Denpasar. This can be seen from the large amount of state foreign exchange income coming from MSME (UMKM)s. In the last decade, many micro businesses have emerged, whether in the form of culinary businesses, fashion, agribusiness, and others. Research with the title "Implementation of Management Systems in CV MSME (UMKM)s. CV. Najwa in the Production of Bali Gebyar Milk Pie in Denpasar", has a problem formulation on how to implement the management system. CV. Najwa is good at production management, human resource management, marketing management and financial management in producing typical Balinese food, namely milk pies, seeing the island of Bali as a tourist destination so it is visited by many tourists. The type of research used is qualitative research. The data collection is by collecting primary data and secondary data. Secondary data was obtained from various reference sources related to the research title. Using purposive sampling as a sampling method. The research results show that implementing management in a company, both large and small companies, is very necessary, because in general every company wants its business to continue running and developing in accordance with the company's goals, to make a profit.